Some Thoughts on Power: International Context - Josifidis, Kosta; Lošonc, Alpar (Panoeconomicus, 2014)
This is a polemical essay that enters into broad dialogue with the contemporary literature concerning the dynamic of power. It refers to the appropriate material and results from the research of different theories. It proposes the constitutive position of the power in the international situation. In contrast to some current theories, we emphasize the importance of the politicoeconomical approach, denoting that only the methodology based on the logics of political economy can explain the dynamics of power in the international context. The main thread of this essay is that the international constellation is not a neutral environment, but a framework that is deeply determined by the power-relations. The central idea is that these relations should be explicated by the complex relationships between freedom and order. We analyze the interaction between the politics and economy as the constitutive feature of the structure of international context. This essay is divided into three sections. First, we are treating the meaning of order in an international context, in respect to the political-economic aspects of late capitalism. The notion of this order has a great importance in the economic reflections. The dynamic of the interconnecttedness of global capitalism is examined considering the systematic aspects of power. After that we are analyzing different, and selected, aspects of the intenational sphere including: the spatiality of the world order, that is, the spatial aspects of the international dynamics in the context of globalization, the convergence or divergence between the capitalist and territorial logic, the “legaleconomic nexus” in international “chain”, the processes of the modification of the forms of competition within recent globalization, and the political-economic conflicts in relation to the regime of economic measurement. Starting with these considerations we explain the current debates on “demondialization”, or the combination between neomercantilist and neoliberal policies.Key words: Power, Order, Capitalism, Crisis, Demondialization.JEL: B50, P16.